KAJIAN LESBIAN GAY BISEKSUAL DAN TRANSGENDER (LGBT) DI PERGURUAN TINGGI: PERSEPSI DAN NIAT MAHASISWA - Wahab Wahab; Irfan Irfan; Eva Gusmira (Jurnal Analisa Sosiologi, 2024)
This research on the perceptions of Islamic Religious College students in Jambi City towards lesbian, gay, bisexual and transgender (LGBT) aims to see the extent of their perceptions (cognitive, affective and conative) and intentions towards LGBT at PTKI Jambi City. This research involved all PTKI students in Jambi City (13,237 students). The sample was determined using proportionate stratified random sampling (389 students). The research method uses a combination (mixed method research) with a sequential explanatory type strategy. Data collection techniques use questionnaires, interviews and documentation. The data analysis technique used is a mixed method technique. Quantitative analysis uses the mean formula followed by qualitative analysis. Influence analysis is seen by evaluating the model by examining the R Square value and analyzing the relationship between variables using the SEM-PLS bootstrapping method. The total mean perception value (3.046) shows that students reject LGBT behavior. Student perceptions have a strong influence on intentions to engage in LGBT as seen from the R Square value (82.4%) and significantly seen from the statistical T value and P values. Students' intention to break the LGBT chain is high (mean value 3.23). The interview results show that government outreach about the dangers of LGBT can be introduced early. Removing LGBT content on social media is also very important to do.